1994
DOI: 10.1152/ajpregu.1994.266.6.r1765
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide Y in hypothalamic paraventricular nucleus: a center coordinating energy metabolism

Abstract: Intracerebroventricular injection of neuropeptide Y (NPY) has two effects on energy metabolism in addition to increased feeding: decreased brown fat thermogenesis and increased white fat lipoprotein lipase (LPL) enzymatic activity. We hypothesized that the paraventricular nucleus (PVN) of the hypothalamus is the controlling neural site for these responses. We further hypothesized that NPY stimulation at PVN would reduce gene expression for the critical brown fat thermogenic protein, uncoupling protein (UCP), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
148
2
1

Year Published

2000
2000
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(161 citation statements)
references
References 28 publications
10
148
2
1
Order By: Relevance
“…It has been suggested that centrally administered NPY increases the expression of LPL mRNA and enhances LPL activity in white adipose tissue thus favoring lipid storage (Billington et al, 1991(Billington et al, , 1994. In the present study, the heparin-releasable LPL activity did not differ among the genotype groups.…”
Section: Leu7pro In Npy Gene and Lipid Response Us Schwab Et Alcontrasting
confidence: 49%
See 2 more Smart Citations
“…It has been suggested that centrally administered NPY increases the expression of LPL mRNA and enhances LPL activity in white adipose tissue thus favoring lipid storage (Billington et al, 1991(Billington et al, , 1994. In the present study, the heparin-releasable LPL activity did not differ among the genotype groups.…”
Section: Leu7pro In Npy Gene and Lipid Response Us Schwab Et Alcontrasting
confidence: 49%
“…However, disturbed liver uptake or catabolism of LDL could also play a role. NPY has been suggested to regulate LPL activity in adipose tissue of experimental animals (Billington et al, 1991(Billington et al, , 1994. This Table 2 Energy intake, proportion of energy nutrients, and the intake of dietary cholesterol and fiber during the run-in period and the reduced fat diet period, mean AE s.e.m.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But the data are clear with respect to CRH and the melanocortin system, and the conclusions are likely to extend to other feeding-relevant neuropeptides. Indeed, there is evidence for such distributed action for two other peptides, CART and NPY, implicated in the mediation of leptin's effects on energy balance (e.g., 11,22,94,191,195). The multiplicity of sites from which a given treatment may trigger the same response has yet to be assimilated into contemporary models for the control of energy balance.…”
Section: Crh/urocortinmentioning
confidence: 99%
“…Of all of these peptides however, NPY is one of the few which actually leads to the development of true obesity and insulin resistance when hypothalamic levels remain chronically elevated [3,28,30,33,40,46,47], as has been reported for various rodent genetic obesity syndromes [2,8,35,42]. The obesity syndrome which results from chronically elevated hypothalamic NPY levels in rodents [3,28,30,33,40,46,47] is still present even when NPY--induced hyperphagia is prevented [3,30,46], demonstrating that hyperphagia is not necessary for central NPY to produce its obesity--like effects. NPY in the hypothalamus is also involved in the regulation of several other important physiological processes including growth [4,22,25], reproduction [4,5,25], and fluid balance [13].…”
Section: Introductionmentioning
confidence: 99%